Avaliação do processo de obtenção de suco de uva gaseificado com elevado potencial antioxidante - Ribas, Maria Fernanda (2018)
Beverage industry in Brazil has been through several transformations and expansion and following the world trend with a greater demand of ready-to-drink juices instead of soft drinks. This is due to the consumer searches for more nutritious products and the provides protective effect on health. This work aimed to develop aerated grape juice, with the cultivars Vitis labrusca BRS Violeta and White Niagara. The juices were extracted using the vapor dragging method and carbonated with carbon dioxide. Juices were characterized and evaluated during refrigerated storage for 150 days. These parameters were evaluated: centesimal composition, physical-chemical proprieties (pH, titratable acidity, soluble solids, insoluble solids, water activity), sugars determination (glucose, fructose and sucrose), in vitro antioxidant activity using ABTS, FRAP and DPPH methodologies and determination of phenolic compounds content. The juices were submitted to sensory evaluation by means of acceptance test, using nine-point hedonic scale and purchase intention. The instrumental analysis was performed by detection of basic tastes (sweet, salty, acid, bitter and umami) in electronic tongue (e-Tongue) and the volatile compounds in electronic nose (e-Nose). As results, considering the vapor dragging method, the juices yield was 50% in both cultivars, and they still had adequate carbonation and could be called “carbonated”. The BRS Violeta aerated grape juice presented high antioxidant potential, higher glucose content than fructose, higher intensity of sweet taste by glucose standard. The Niagara Branca aerated grape juice presented higher fructose content than glucose, even higher intensity of sweet taste by fructose standard. Phenolic compounds degradation was evidenced through the storage in both juices, however, the cultivar used is a definitive factor to obtain antioxidant potential. Considering the sensory analysis, the Niagara Branca aerated grape juice presented greater acceptance regarding the sensorial attributes evaluated and the greater intention to buy it compared to cultivar BRS Violeta. However, the juices of both cultivars demonstrated market potential, due to the acceptance rate above 80%. Sensory analysis by words association technique allowed consumers a better perception regarding to the terms “juice” and “nectar”. As conclusion, the grape juice carbonation technique using back pressure was efficient, and reached adequate gas volume, therefore, let to the development of naturally healthy drink, which can meet the consumers demand, with the attractive differential of juice being carbonated.